Reconhecimento científico e avaliação post-mortem em obituários acadêmicos da revista pesquisa FAPESP: estudo bibliométrico e de conteúdo - Hayashi, Maria Cristina Piumbato Innocentini (2021)
In the academic context, the obituaries of scientists and intellectuals express the scientific recognition of those who contributed to expanding knowledge in their areas of expertise, and at the same time they can reveal a type of post-mortem evaluation. Based on the Sociology of Science framework and the contributions of bibliometric and content analysis, this article analyzes the academic obituaries (n=131) published in the Revista Pesquisa FAPESP between 1999 and 2021. The main results showed that the obituaries of men (n=109) prevailed over those of women (n=22). 96% of obituaries were born between the 1910s and 1950s, and the majority (n=123) died between 1990 and 2010. The most common causes of death were cardiovascular diseases and cancer, and the age of death varied between 45 and 100 years, suggesting a high longevity among scientists and intellectuals, revealing the occurrence of the phenomenon of academic intergenerationality. The personal and academic virtues, scientific leadership, and inspirational role of deceased scientists and intellectuals revealed recognition expressed in micronarratives of talent and merit that can be considered a post-mortem assessment of academic achievement.